"Your Shadow Blocks My Sun": Reading Alternative Narratives in The New Parthenon and Other Films by Penny Siopis. Issue 3 (2nd September 2022) - Bronner, Irene Enslé
Abstract: In The New Parthenon, as with her other films, Penny Siopis pieces together fragments of found footage of anonymous home videos, shot handheld on 8 or 16 mm film. The films are digitised first for sampling, but not digitally remastered, and are then combined with music and subtitles from various sources. These films narrate the stories of individuals, set against significant historical and political events. Evocativeness and anxiety are induced by the un-specificity of the connections between images and subtitles, heightened by the materiality of the amateur home video footage, often centred on quotidian family life and holidays, that has been reframed to narrate events that continue to reshape nations. I introduce the construction of a nation as a political community and examine how Siopis subverts narratives that connect ancient and contemporary Greece and its own internal antisemitic and nationalist conflicts to those of apartheid South Africa and imperialist Britain. I propose that the numerous representations of souvenir replicas and icons in The New Parthenon appear to perform a witnessing role to public and personal histories, while symbolically holding historical traumas in frozen form. I focus on Siopis's mediated views of the Acropolis structures in the film, considering the symbolic bleaching of the Parthenon Marbles in the nineteenth-century British imaginary to track whiteness as a signifier of power. Siopis migrates this to signifiers of apartheid South Africa in order, I argue, to critique the narratives that maintain national imaginaries and to propose instead an aesthetics of reattachment.